"Jantra" as Coastal Education Equipmment and Creative Empowerment of Fishers Children Indrama - Danang Kuntoro Wedi; Irfan Syauqi; Novia Putri Sari; Tyas Putri Jayanti; Cahya Sutardi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
MI Al-Ikhlas Eretan Wetan is a school located in Eretan Wetan Village, Kandanghaur Subdistrict, Indramayu District, West Java. The majority of students who attend school there are fishermen who have very little knowledge of fisheries. So that the impact on the low interest of children in the world of fisheries. This is evidenced by the survey results of students of the Department of PSP-IPB from 30 children interviewed 100% have not understood marine fisheries. This condition is very apprehensive considering the fishery sector is a major sector for Indonesia as a maritime country. One effort to foster interest and knowledge of marine fisheries to children is through Jantra Education. Jantra's education includes play activities while studying fisheries such as environmental education, marine education delivered through a Jantra game, as well as training of trainers to teachers, and advocacy to relevant institutions for sustainability and expansion of the program. The program's activities resulted in an innovative marine educational media and increased knowledge and interest in marine fisheries.